STUDIES ON SCROTAL BIOMETRY, EJACULATE CHARACTERISTICS AND FERTILITY IN ONGOLE BULLS - THIRUMALA RA0, T; MUTHA RAO, M; BABU RAO, K; NAIDU, K V (The Indian Journal of Animal Reproduction, 2023)
Scrotal biometry and ejaculate characteristics were studied in 25 Ongole breed bulls stationed in a Livestock Research station and correlated them with fertility. The scrotal and testicular measurements revealed mature size by 5 years of age. A significant difference was observed between bulls in relation to various ejaculate characteristics like mass activity, initial motility, live sperm count and sperm abnormalities. The mean fertility rate to first insemination was found to be 71.63%. I twas further observed that scrotal biometry, sperm concentration, progressive motility and live sperm count were positively correlated to first Al conception rate in cows.